Physical Spaces in Higher Education as Scenarios of Learning Innovation: Compositional and Formative Synergies among Architecture, Music, and Fashion - Pablo Campos; Laura Luceño; Carlos Aguirre (MDPI AG, 2021)
Learning innovation is a positive approach on the contemporary higher education international stage. This article stresses the need to devise physical spaces that are also innovative. For that purpose, using a qualitative methodology, we investigated recent trends based on the synergies between certain creative disciplines: architecture, music, and fashion. The comparison was based on compositional features and formative dimension. Using a qualitative methodological comprehensive approach, a set of case studies was analysed. The findings show the usefulness of activating these synergies as effective strategies when enriching educational processes in different ways. Six cases of excellence wherein university physical spaces reached levels of innovation were studied, representing relevant transfers among the three disciplines. The text presents examples that show the educational consequences in the establishment of those synergies, in terms of both composition (music-architecture) and the activation of heritage sites in the city as venues of learning innovation (fashion-architecture). The basic conclusions were based on the fact that the increase in teaching and spatial creativity that emanates from said synergies among the three disciplines can be potentially extrapolated to other areas of knowledge.